2021
DOI: 10.5812/zjrms.104193
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Music Therapy on Sense of Loneliness and Life Expectancy in Methamphetamine-Addicted Individuals Attempting to Quit

Abstract: Background: Since there has been no research on music therapy in a systematic way so far to develop motivation and hope in the course of treating individuals who are addicted to drugs, especially stimulant drugs whose use has increased in Iran, the present research was conducted to examine the effect of music therapy on the sense of loneliness and life expectancy in methamphetamine-addicted individuals who were attempting to quit. Methods: The research is pretest, posttest, and test and control groups. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Jones (2005) found that a songwriting intervention lessened feelings of loneliness among participants with substance dependence. Mohammadirad and colleagues (2021) also found that music therapy interventions including guided imagery and music listening followed by lyric discussion led to decreased loneliness among individuals with methamphetamine addictions. In a study on the effects of music therapy on engagement for participants with SUD, Dingle et al (2008) found that almost half of participants believed continued music therapy sessions would facilitate a sense of group membership.…”
Section: Review Of Literaturementioning
confidence: 91%
“…Jones (2005) found that a songwriting intervention lessened feelings of loneliness among participants with substance dependence. Mohammadirad and colleagues (2021) also found that music therapy interventions including guided imagery and music listening followed by lyric discussion led to decreased loneliness among individuals with methamphetamine addictions. In a study on the effects of music therapy on engagement for participants with SUD, Dingle et al (2008) found that almost half of participants believed continued music therapy sessions would facilitate a sense of group membership.…”
Section: Review Of Literaturementioning
confidence: 91%
“…We have read a recently published article in Zahedan Journal of Research in Medical Sciences by Mohammadirad et al, entitled "The Effect of Music Therapy on Sense of Loneliness and Life Expectancy in Methamphetamine-Addicted Individuals Attempting to Quit" (1). Mohammadirad et al showed an absorbing inquiry on reducing the sense of loneliness and increasing life expectancy in methamphetamine addicts attempting to quit (1). They deduced that "music therapy can improve various psychological dimensions and, as a therapeutic approach, is able to meet the needs of addicts.…”
Section: Dear Editormentioning
confidence: 99%